Thermal comfort and productive responses of 7/8 holstein-gyr cows subjected to cooling system - Silva, Marcos Vinícius da; Almeida, Gledson Luiz Pontes de; Pandorfi, Héliton; Moraes, Alex Souza; Macêdo, Gleidiana Amélia Pontes de Almeida; Oliveira, Maria Eduarda Gonçalves de; Melo, Maria Vitória Neves de; Santana, Taize Calvacante (Acta Scientiarum. Animal Sciences, 2023)
The objective of this research was to identify the influence of the evaporative adiabatic cooling system (EACS) on the thermal comfort and productive responses of dairy cattle, through multivariate analysis by principal components (PC), in the summer and winter seasons of the semiarid region of Pernambuco, Brazil. The data came from an experiment that included 16 multiparous lactating cows (7/8 Holstein-Gyr), randomly distributed in 4 sets, with 4 experimental phases and 4 treatments (0, 10, 20, and 30 min.). The multivariate analysis was carried out through PC for the thermal comfort indices, physiological variables, and milk production and composition. The highest milk production in the summer season was obtained for animals exposed to the cooling system for 30 min. In the winter season in the morning period, the use of the EACS for 10 min. was sufficient for improvements in milk production. The times of exposure to EACS caused changes in the composition of milk, for both seasons. Principal component analysis made it possible to verify a positive correlation of evaporative cooling with thermal comfort, physiological responses, and production and composition of milk of lactating cows.